UJI IRITASI SEDIAAN GEL ANTIJERAWAT FRAKSI LARUT ETIL ASETAT EKSTRAK ETANOL DAUN BINAHONG (Anredera cordiofolia (Ten.) Steenis) PADA KELINCI - Nur Ermawati (LPPM Universitas Pekalongan, 2018)
Gel is a pharmaceutical preparation with good penetration power and long contact time with skin so it can overcome the problem of acne. Gelling agent is the main ingredient in gel preparation. Skin irritation test is an important part of the pharmaceutical preparation procedures. In Material Safety Data Sheet states that Hydroxy Propyl Methyl Cellulose (HPMC) and Carbopol can cause skin irritation problems. The aim of this research is to find out whether gel preparation of the active fraction of ethanol extract of binahong leave with combination of gelling agent Hydroxy Propyl Methyl Cellulose (HPMC) and carbopol can cause irritation on rabbit skin. The irritation test was performed by Draize method on three New Zealand male rabbits who had shaved the back part 24 hours prior to treatment. The irritant samples were smeared and then covered with sterile gauze and glued with plaster. Observations were made after 24, 48 and 72 hours after administration of the test material. Each area observed skin reactions that occur and scored 0 to 4 depending on the severity of skin reactions produced. Of the three gel preparation formulas, the score of degree of irritation was 1, 1 and 1.67, which means slight irritation (0.41-1.9).Keywords: binahong leave, gelling agent, irritation test.